2021
DOI: 10.14507/epaa.29.5315
|View full text |Cite
|
Sign up to set email alerts
|

Competências genéricas auto referidas por universitários brasileiros

Abstract: Although there is no standardization of the notion of competence and for the instruments used in its evaluation, generic competences are associated with employability, and understood as a composition of cognitive and practical abilities, behavioral and social skills, gathering individual characteristics and qualities required for activities of different professions. Education promotes the development of specific competences for the exercise of certain occupations, in addition to opportunities for increasing ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Domestic scholars unanimously encourage vocational education institutions to attach importance to skills competitions to enhance employment quality, but there is little research analyzing the impact of skills competitions on the early labor market performance of secondary vocational school graduates at the high school level. General abilities are closely related to employability, and previous studies have found that general abilities promote employment quality [49], such as general skills contributing to the employment quality of future accountants and auditors [50]. However, faced with the "skill degradation" under the impact of automation technology in modern industrial labor [51] and the school atmosphere of "emphasizing academics over skills" in vocational schools, how much do the skills of secondary vocational school students affect their employment quality?…”
Section: Related Studiesmentioning
confidence: 99%
“…Domestic scholars unanimously encourage vocational education institutions to attach importance to skills competitions to enhance employment quality, but there is little research analyzing the impact of skills competitions on the early labor market performance of secondary vocational school graduates at the high school level. General abilities are closely related to employability, and previous studies have found that general abilities promote employment quality [49], such as general skills contributing to the employment quality of future accountants and auditors [50]. However, faced with the "skill degradation" under the impact of automation technology in modern industrial labor [51] and the school atmosphere of "emphasizing academics over skills" in vocational schools, how much do the skills of secondary vocational school students affect their employment quality?…”
Section: Related Studiesmentioning
confidence: 99%
“…Percebe-se um cenário extremamente complexo, desafiador e imprevisível com que se deparam as universidades e instituições envolvidas no processo de formação profissional para o mercado. Elas preparam um profissional que se deparará com a necessidade de desenvolver novas competências mesmo depois de formado, de minimizar as lacunas da formação recebida, de entender e se adequar a um mercado com oportunidades restritas (Carvalho et al, 2021). E mesmo diante de todas as dificuldades que lhe são inerentes, as universidades precisam se adequar e se reinventar para poderem dar a resposta que a sociedade espera delas.…”
Section: Formação Profissional Para O Futurounclassified
“…A graduação universitária, mesmo sendo um diferencial, não supre as inúmeras exigências para essa inserção e posterior permanência no trabalho. Dentre as exigências está o desenvolvimento de competências ao longo do processo formativo que vão além daquelas somente técnicas (Carvalho et al, 2021). As empresas deste século "buscam que os trabalhadores tenham amplos atributos de ordem sistêmica e interpessoal, como competências pessoais e transferíveis, em detrimento a habilidades puramente instrumentais, aquelas relacionadas diretamente à capacitação da formação" (Carvalho et al, 2021, p. 4).…”
Section: Competências Profissionaisunclassified
“…A formação de professores na educação superior desempenha papel central em políticas educacionais voltadas para a melhoria da qualidade e equidade do exercício da docência em sala de aula. Ainda que a simples titulação acadêmica seja insuficiente para avaliar a eficácia do professor, a realização de curso de graduação compatível com a área em que leciona está associada a fatores de importância reconhecida para os resultados educacionais dos estudantes, sobretudo aqueles mais carentes, como o domínio do conteúdo e a adoção de métodos e recursos didáticos eficazes (PAUL;BARBOSA, 2008;CARVALHO et al, 2021). Não é por acaso, portanto, que a ampliação da formação específica de nível superior para professores da educação básica esteja consagrada na meta 15 do Plano Nacional de Educação (BRASIL, 2014), e que iniciativas recentes de regulação da formação docente, como as Diretrizes Curriculares Nacionais para a Formação Inicial de Professores para a Educação Básica e a Base Nacional Comum para a Formação Inicial de Professores da Educação Básica (BNC-Formação) (BRASIL.…”
Section: 1 Introduçãounclassified